How many more livesn [videorecording] - Griffiths, Steven ([S.l.] Frontier Productions, 1990)
An insight on the plight of mining workers of Atlas Mining Corp. in Cebu Island. It provides a look into the miners attempt to establish a pro-workers union.
Narration, Marla Baranilla; editing, Christine Duval, Nonoy Regalado.
Keywords: Trade unions -- Miners -- Atlas Cooper Mines (Cebu).; Mines -- Philippines -- Cebu; Labor relations; Sociology